A Pilot Study on the Safety and Adequacy of a Novel Ecofriendly Hemodialysis Prescription–Green Nephrology - Dolphin Solomon; Venkatesh Arumugam; Ramanathan Sakthirajan; Tanuj Moses Lamech; Thanigachalam Dineshkumar; Paulpandiyan Vathsalyan; Guhan Senthilkumaran; Ravindran Krishna; Sajmi Shaji; Natarajan Gopalakrishnan (Kidney International Reports)
Introduction: Hemodialysis (HD) units require large quantities of water. To reduce water consumption without compromising the adequacy and safety of dialysis, we studied a novel HD prescription with high temperature and low flow dialysate. Methods: This was a single-center nonrandomized open-label cross-over pilot trial in patients with end-stage kidney disease on maintenance HD. Each participant was subjected to 3 different dialysis prescriptions for 1 month each as follows: (i) normal temperature with normal flow dialysate (NTNF prescription), (ii) high temperature with normal flow dialysate (HTNF prescription), and (iii) high temperature with low flow dialysate (HTLF prescription). The primary outcome, assessed at the end of each dialysis session, was the delivery of “adequate” dialysis, as defined by a single-pool Kt/V (spKt/V) ≥1.2. Outcomes were evaluated by comparing the NTNF and HTLF prescriptions. Results: A total of 863 sessions of HD were performed in 30 patients over 3 months, with 287 to 288 sessions in each of the 3 dialysis prescriptions. The primary outcome was not significantly different between the NTNF prescription (202 sessions [70.14%]) and the HTLF prescription (198 sessions [68.75%]) (odds ratio, 1.07; 95% confidence interval, 0.75 to 1.52; P = 0.45). The mean spKt/V and urea reduction ratio (URR) were not significantly different. Clinically evident hemodynamic instability occurred in only 1 dialysis session in the HTNF prescription. Conclusion: Increasing dialysate temperature while reducing dialysate flow rate (QD) can be used as a water conservation strategy without compromising the adequacy and safety of dialysis in young and hemodynamically stable patients. Reducing the QD from 500 ml/min to 300 ml/min reduces water consumption by 40%.